Determinants of Food Security in Rural Households: An Analysis of Dietary Diversity, Land Ownership, and Socioeconomic Factors - Deviantony, Fitrio; Dewi, Erti Ikhtiarini; Fitria, Yeni; Kurniyawan, Enggal Hadi (Al-Hijrah Indonesia, 2024)
Background: Food security is a critical issue in rural areas, influenced by various socioeconomic factors, dietary practices, and resource ownership. Understanding the determinants of food security can help in designing effective interventions to improve the well-being of rural households. Purpose: This study aims to identify and analyze the key determinants of food security among rural households, focusing on dietary diversity, land ownership, and other socioeconomic factors. Methods: The dataset used in this study includes variables such as gender, marital status, education, land ownership, food crop cultivation, meal frequency, age, food source, Food Security Index (FSI), and Household Dietary Diversity Score (HDDS). Multiple linear regression analysis was conducted to explore the relationships between these variables and the FSI. Additionally, a Random Forest Regressor model was employed to predict the FSI and to determine the importance of each feature. Results: The multiple linear regression analysis revealed that HDDS has a significant positive relationship with the FSI (p<0.001), indicating that higher dietary diversity is associated with higher food security levels. Other variables, such as education and food source, showed weaker correlations with food security. The Random Forest Regressor model achieved an R-squared value of 0.495, with feature importance analysis indicating that HDDS, food source, and age are the most influential factors in determining food security. The Mean Squared Error (MSE) of the model was 10.743. Conclusion: This research highlights the crucial role of dietary diversity and socioeconomic conditions in shaping food security outcomes in rural areas. The findings provide valuable insights for policymakers and stakeholders aiming to enhance food security and dietary quality in rural communities. Further studies are recommended to explore the complex interactions between these variables and to develop targeted interventions to improve food security.